Characterizing Aging in the Human Brainstem Using Quantitative Multimodal MRI Analysis - Lambert, Christian; Chowdhury, Rumana; Fitzgerald, Thomas; Fleming, Stephen M.; Lutti, Antoine; Hutton, Chloe; Draganski, Bogdan; Frackowiak, Richard; Ashburner, John (Frontiers in Human Neuroscience, 2013)
Ageing is ubiquitous to the human condition. The MRI correlates of healthy ageing have been extensively investigated using a range of modalities, including volumetric MRI, quantitative MRI and DTI. Despite this, the reported brainstem related changes remain sparse. This is, in part, due to the technical and methodological limitations in quantitatively assessing and statistically analysing this region. By utilising a new method of brainstem segmentation, a large cohort of 100 healthy adults were assessed in this study for the effects of ageing within the human brainstem in vivo. Using quantitative MRI (qMRI), tensor based morphometry (TBM) and voxel based quantification (VBQ), the volumetric and quantitative changes across healthy adults between 19-75 years were characterised. In addition to the increased R2* in substantia nigra corresponding to increasing iron deposition with age, several novel findings were reported in the current study. These include selective volumetric loss of the brachium conjunctivum, with a corresponding decrease in magnetisation transfer (MT) and increase in proton density (PD), accounting for the previously described “midbrain shrinkage”. Additionally, we found increases in R1 and PD in several pontine and medullary structures. We consider these changes in the context of well-characterised, functional age-related changes, and propose potential biophysical mechanisms. This study provides detailed quantitative analysis of the internal architecture of the brainstem and provides a baseline for further studies of neurodegenerative diseases that are characterised by early, pre-clinical involvement of the brainstem, such as Parkinson’s and Alzheimer’s diseases.